Redescription of Magelona minuta Eliason, 1962 (Annelida), with discussions on the validity of Magelona filiformis minuta - Mills, Kimberley; Mortimer, Kate (Zootaxa, 2018)
Since Magelona minuta was described in 1962 our understanding of the key features required to distinguish between magelonid species has increased. The original description contains only four illustrations and vital information on many key characters is not included. This re-assessment of the holotype and material from the type locality includes several features not previously described, specifically related to thoracic and abdominal lamellae. Comparative material from Britain and the Southern Irish and Celtic Seas is examined, adding information on the posterior region. Diet is discussed based on the gut contents of a specimen originally identified by Eliason. Information on numbers of thoracic chaetae and the angle between teeth of abdominal hooded hooks for several magelonid species is investigated. The validity of the dwarf species Magelona filiformis minuta is herein examined.